Experimental Study on the Residual Property of Kevlar-Jute/Epoxy Hybrid Composite Laminates with Multiple Drilled Holes - Mahdi Hosseini; Milan Gaff; Petr Konvalinka; Haitao Li; Hynek Maňák; Jensin Joshua; Keerthana M R; Ahmad Hosseini; Pritam Ghosh; David Hui (Journal of Natural Fibers)
The study estimates the residual property of [Jute/Kevlar/Jute] and [Kevlar/Jute/Kevlar] hybrid composite laminates with multiple drilled holes. The laminates are prepared using a compression molding technique with Kevlar and Jute as reinforcements in two different stacking sequences. Post-fabrication, holes are drilled with two different center diameters 4 mm and 12 mm and multiple holes are drilled with two different effective lengths from the center hole, i.e. 2 mm and 4 mm. Compression testing is conducted using a Universal Testing Machine (UTM) to assess the compression strength of the specimens without drilled and with drilled specimens. The damage reduction factor, residual strength ratio, residual load carrying capacity and the effective stress post damage are then evaluated for the laminates with drilled holes at different effective lengths. The article is intended to suggest possible reduction in strength on introduction of natural fiber in an existing construction so that based on requirement, existing structures can be optimized. The study aims to measure the reduction in compressive residual strength due to stress concentrations introduced by drilling. Testing showed that the laminate configuration KK05 exhibited the highest residual compressive strength, retaining approximately 85% of its original strength after drilling, making it ideal for applications requiring high durability.